Codes of Misconduct : Regulating Prostitution in Late Colonial Bombay - Tambe, Ashwini (Book collections on Project MUSE., 2009)
Across the nineteenth and twentieth centuries, legislators in Bombay passed a series of repetitive laws seeking to control prostitution. During the same time, Bombay's sex industry grew vast in scale. Ashwini Tambe explores why these remarkably similar laws failed to achieve their goal and questions the actual purpose of such lawmaking. Against the backdrop of the industrial growth of Bombay, Codes of Misconduct examines the relationship between lawmaking, law enforcement, and sexual commerce. Ashwini Tambe challenges linear readings of how laws create effects and demonstrates that the regulati.